PERTUMBUHAN INSITITUSI PENDIDIKAN AWAL DI INDONESIA :PESANTREN, SURAU DAN DAYAH - Muslim Muslim (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
The presence and emergence of Islamic education in Indonesian soil is closely related to the entry of Islam on earth. The process of Islamization of society at that time was an integral part of the implementation of Islamic education. This paper is of a qualitative type, with a library research approach. Several early education institutions in Indonesia. First, pesantren may have originated from India (Hindu influence in Java), but the education system is certain to come from the Islamic tradition that originated in Arabic. There is an argument to support this hypothesis that Islam came to Java for the first time brought by Shaykh Malik Ibrahim or Maulana Maghribi (one of the songo guardians) and he had studied in the Kingdom of Pasai. Both Surau come from elements of the indigenous Malay culture and are related to the belief at that time as an Islamic educational institution. The three Dayahs are the oldest Islamic educational institutions in Aceh and even in the archipelago. Dayah was born, grew and developed along with the entry and development of Islam in Acehnese society.